WHEN TIME DOESN'T HEAL: A CASE REPORT ON THE USE OF TRAUMA PROCESSING THERAPY FOR PROLONGED GRIEF DISORDER MISDIAGNOSED AS DYSTHYMIA - Ardian, Jiemi (Journal of Psychiatry Psychology and Behavioral Research, 2025)
Background: Prolonged grief disorder (PGD) can be mistakenly diagnosed as other mood disorders, leading to ineffective treatment approaches. Traditional interventions, including antidepressants and general psychotherapy, may not adequately address the underlying trauma associated with loss. The aim of this paper was to demonstrate the effectiveness of Trauma Processing Therapy (TPT) in treating prolonged grief disorder that was initially misdiagnosed as dysthymia. Methods: A case study of a 30-year-old male with persistent depression symptoms following his father's death 24 years prior. Initially diagnosed with dysthymia and treated unsuccessfully with escitalopram and cognitive-behavioral therapy, the patient was later diagnosed with PGD. Treatment involved a single session of Trauma Processing Therapy, incorporating memory reconsolidation, ego state therapy, and hypnoanalysis techniques. Results: Following one session of TPT intervention, the patient showed significant improvement, with Prolonged Grief Inventory scores decreasing from 54 to 11 and Beck Depression Inventory scores reducing from 61 to 10. The patient demonstrated improved emotional regulation, increased ability to engage in meaningful activities, and better acceptance of the loss. Follow-up assessments at 3 and 6 months showed maintained improvements. Discuss: Trauma Processing Therapy enabled the client to safely confront and integrate the emotional memories surrounding his father’s death, resulting in a substantial and enduring reduction in grief symptoms. Conclusion: Trauma Processing Therapy proves effective in treating prolonged grief disorder by addressing unprocessed trauma through memory reconsolidation, leading to significant and sustained improvement in grief symptoms and overall functioning.